An introductory report on the effect of use of dextranase-containing mouthwash on oral health status of human volunteers - Juntarachot, Nucharee; Sivamaruthi, Bhagavathi Sundaram; Sirilun, Sasithorn; Tongpong, Piyachat; Sittiprapaporn, Phakkharawat; Kantachote, Duangporn; Chaiyasut, Chaiyavat (Asian Journal of Medical Sciences, 2020)
Background: Dextran is a branched polysaccharide and one of the polymers, present in the biofilm matrix. The dextran plays a perilous role in dental plaque formation, which is involved in the development of some common oral diseases like dental caries. The dextran-hydrolyzing enzymes are under investigation to treat and manage the dental plaques. Aims and Objective: The present study reporting the preliminary observations on the effect of the use of dextranase-containing mouthwash (DMW) on dental plaque and oral health. Materials and Methods: DMW was prepared with food-grade dextranase, preservatives, gellingagents, and water as detailed. Four weeks of experimental design was employed in fourteen healthy volunteers. The selected volunteers were recommended to use DMW for at least twice a day. The plaque index (PI), probing depth (PD), gingival index (GI) and bleeding on probing (BOP) of the volunteer's teeth have been assessed before and after four weeks of DMW use. Results:The volunteers were insisted to use a DMW solution twice a day for four weeks. The PI, PD, GI, and BOP was measured before and after the treatment. The plaque index of the subject at baseline and after treatment was 2.22 ± 0.48, and 1.88 ± 0.50, respectively. PI was significantly reduced after the use of DMW solution for four weeks. The value of PD was 2.00 and 2.00 at baseline and after the use of DMW, respectively. The value of PD was not changed when compared to the baseline values. The sensory evaluation of DMW was performed using questionnaires. Conclusion: The preliminary study results suggested that the use of DMW solution for four weeks (twice a day) notably reduced the PI without any change in PD. However, GI and BOP values were not affected after the use of DMW. The participants, based on the sensory evaluation, accepted the prepared DMW solution. Additional detailed research on the impact of DMW on oral hygiene is needed to confirm the beneficial effects of DMW.